Effect of laparoscopy versus laparotomy on circulating tumor cells using isolation by size of epithelial tumor cells. Issue 2 (1st February 2004) - Lelievre, L.; Paterlini-Brechot, P.; Camatte, S.; Tartour, E.; Aggerbeck, M.; Vilde, F.; Lecuru, F.
Abstract : Aim: To assess the effect of laparoscopy on circulating tumor cell (CTC) detection in case of carcinosis. Material and methods: We compared laparoscopy versus laparotomy on tumor cell blood release in an animal model of ovarian carcinosis obtained by intraperitoneal inoculation of IGR-OV1 cells in nude rats. Animals were randomly assigned to one of the following groups: CO2 laparoscopy (L), gasless laparoscopy (GL), midline laparotomy (ML), or general anesthesia as control (C). A 0.5 ml blood sample was taken in each case before and after experiment and tested with a novel assay, ISET (isolation by size of epithelial tumor cells), which isolates CTC by filtration on account of their size. Statistics were performed with the Fisher's and the Chi-square tests. Results: Ten rats were included in each group. We did not find any significant difference in CTC prevalence before and after surgery (2/14 versus 3/19, respectively, P = 1). Similarly, the three surgical accesses were equivalent with one postexperiment detection per group: 1/5 for L, 1/7 for ML, 1/7 for GL, and 1/6 for C ( P = 0.9). Conclusion: This trial did not show any deleterious effect of laparoscopy on CTC when compared to laparotomy.